Achievement Sports Development Policy by KONI Depok City during the Pandemic Period - Muhammad Imam; Amri Yusra; Donni Edwin; Syaiful Bahri; Ali Muhyidin (JUARA : Jurnal Olahraga, 2023)
This study aims to analyze the development of achievement sports during the COVID-19 pandemic in Depok City. The unit of analysis for this research is the coaching policy applied to the development of achievement sports by the Depok City Indonesian National Sports Committee (KONI) during the COVID-19 pandemic. This research is qualitative descriptive research, and interviews and document study obtained data collection. The study results found that the Depok City KONI during the COVID-19 pandemic focused more on coaching athletes with a target of ranking in the top 10 in the West Java Province Regional Sports Week (Porda) in 2022. This study concludes that the policy of developing achievement sports for the Depok City KONI during the pandemic has been relatively good despite experiencing difficulties in dealing with several obstacles, such as decreased athlete motivation, hampered athlete development due to competition cancellations, restrictions on the use of sports infrastructure, and shifts in funding allocations during the COVID-19 pandemic.